2017
DOI: 10.1093/heapol/czx101
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS National Strategic Plans of Sub-Saharan African countries: an analysis for gender equality and sex-disaggregated HIV targets

Abstract: National Strategic Plans (NSPs) for HIV/AIDS are country planning documents that set priorities for programmes and services, including a set of targets to quantify progress toward national and international goals. The inclusion of sex-disaggregated targets and targets to combat gender inequality is important given the high disease burden among young women and adolescent girls in Sub-Saharan Africa, yet no comprehensive gender-focused analysis of NSP targets has been performed. This analysis quantitatively eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The Human Immunodeficiency Virus (HIV), a very common communicable disease, remains one of the major public health challenges [1]. By the end of 2018, about 37.9 million people worldwide were living with HIV, with sub-Saharan Africa being the most affected region, with 25.6 million people living with HIV in the region, sharing two-thirds of all cases worldwide [2].…”
Section: Introductionmentioning
confidence: 99%
“…The Human Immunodeficiency Virus (HIV), a very common communicable disease, remains one of the major public health challenges [1]. By the end of 2018, about 37.9 million people worldwide were living with HIV, with sub-Saharan Africa being the most affected region, with 25.6 million people living with HIV in the region, sharing two-thirds of all cases worldwide [2].…”
Section: Introductionmentioning
confidence: 99%
“…62 An analysis of the HIV/AIDS National Strategic Plans (NSP) of Sub-Saharan African countries noted the dire need for incorporation of gender equality and sex-disaggregated targets across the region's NSP to enable outcome monitoring and evaluation among both men and women. 64 Due to societal stigmatization, survivors of sexual assault in Nigeria are sometimes reluctant to report the incidence to a health care provider or law enforcement agent leading to delay in accessing health services. 11 From the perspective of HIV infection, delay is dangerous since PEP drugs must be initiated within 72 hours of exposure to HIV risk of infection to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found differences in how men and women living with HIV perceive and experience HIVrelated stigma [13,18,19]. For example, among PLWH in the United States, HIV disclosure concerns were associated with increased health-related worries among women, but not among men living with HIV [20].…”
Section: Introductionmentioning
confidence: 98%